Sight Beyond Sight: Foreseeing Fraudulent Financial Reporting through the Perspective of Islamic Legal Ethics - Dien Noviany Rahmatika; Achmad Irwan Hamzani; Havis Aravik; Nur Rohim Yunus (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2020)
Abstract. In the financial sectors, fraud has become a world phenomenon, ranging from fraudulent financial reports, assets misappropriation and corruption. These three types of fraud are practices carried out deliberately against the law which harm many parties. This study aims to analyze fraudulent financial reporting, where the presentation of misstatements is presented to mislead financial reports. These are against the ethical perspective of Islamic law as stated in the Quran and Hadith. This research uses secondary data based on the principles of sharia accounting concepts and Islamic ethics. The analytical method used is a qualitative description method with literary and normative approaches by examining fraudulent financial reporting from the perspective of Islamic law. The results of this study strengthen the theory of fraud pentagon with the symptoms and red flags of fraud, namely pressure, opportunity, rationalization, competence, and arrogance of the perpetrators of fraud. The Quran as well as the hadith emphasize the values of honesty, justice, truth, responsibility, and belief in reporting. This research also overlooks the weak ethics of the accounting profession and also the value of religiosity held by weak accountants from the perspectives of Islam.Keywords: Accounting Fraud, Fraudulent Financial Reporting, Fraud Pentagon Theory, Islamic Legal Ethics Abstrak. Pada sektor keuangan, fraud (kecurangan) menjadi salah satu fenomena global, dengan kasus kecurangan laporan keuangan, penyelewengan aset dan korupsi. Ketiga bentuk kecurangan tersebut merupakan praktek yang dilakukan secara sengaja melawan hukum dan merugikan banyak pihak. Penelitian ini bertujuan untuk menganalisis kecurangan pelaporan keuangan, dimana informasi yang disajikan dalam laporan adalah hal yang tidak sesuai dengan kenyataan. Hal ini bertentangan dengan etika hukum Islam dalam Al-Qur'an dan Hadits. Penelitian ini adalah menggunakan data sekunder dengan mendasarkan pada prinsip-prinsip akuntansi syariah dan etika Islam. Metode analisis yang digunakan adalah metode deskripsikualitatif dengan pendekatan literatur dan kajian normatif. Hal ini dilakukan dengan memeriksa kecurangan pelaporan keuangan dari perspektif hukum Islam. Hasil dari penelitian ini memperkuat teori Fraud Pentagon tentang gejala dan Red Flag Fraud, yang terdiri dari tekanan, peluang, rasionalisasi, kompetensi, dan arogansi para pelaku penipuan. Hal ini bertentangan dengan prinsip hukum Islam yang menekankan pada nilai-nilai kejujuran, keadilan, kebenaran, tanggung jawab, dan kepercayaan dalam pelaporan. Penelitian ini juga menunjukkan lemahnya prinsip etis dalam profesi akuntansi dan jugai religiusitas yang dimiliki oleh akuntan.Kata kunci: Kecurangan akuntansi, Kecurangan Pelaporan Keuangan, Teori Fraud Pentagon, Etika Hukum Islam